Genome analysis and genomic comparison of a fungal cultivar of the nonsocial weevil Euops chinensis reveals its plant decomposition and protective roles in fungus-farming mutualism - Guo, Wenfeng; Wang, Wei; Tang, Jun; Li, Tianyu; Li, Xiaoqiong (Frontiers in Microbiology, 2023)
Fungus-farming mutualisms are models for studying co-evolutionary among species. Compared to well-documented fungus-farming in social insects, the molecular aspects of fungus-farming mutualisms in nonsocial insects have been poorly explored. Euops chinensis is a solitary leaf-rolling weevil feeding on Japanese knotweed (Fallopia japonica). This pest has evolved a special proto-farming bipartite mutualism with the fungus Penicillium herquei, which provide nutrition and defensive protection for the E. chinensis larvae. Here, the genome of P. herquei was sequenced, and the structure and specific gene categories in the P. herquei genome were then comprehensively compared with the other two well-studied Penicillium rspecies (P. decumbens and P. chrysogenum). The assembled P. herquei genome had a 40.25 Mb genome size with 46.7% GC content. A diverse set of genes associating with carbohydrate-active enzymes, cellulose and hemicellulose degradation, transporter, and terpenoid biosynthesis were detected in the P. herquei genome. Comparative genomics demonstrate that the three Penicillium species show similar metabolic and enzymatic potential, however, P. herquei has more genes associated with plant biomass degradation and defense but less genes associating with virulence pathogenicity. Our results provide molecular evidence for plant substrate breakdown and protective roles of P. herquei in E. chinensis mutualistic system. Large metabolic potential shared by Penicillium species at the genus level may explain why some Penicillium species are recruited by the Euops weevils as crop fungi.